A comprehensive study on key management, authentication and trust management techniques in wireless sensor networks - Gautam, Amit Kumar; Kumar, Rakesh (SN applied sciences, 2021)
Wireless sensor networks (WSN) are the new speed-accelerating technologies worldwide and are used continuously in a range of critical applications. Any damage or compromise to data security could have physical and direct effects on network efficiency and safety. One of the active areas of research is key management, authentication, and trust management in wireless sensor networks (WSN). Since researchers have provided many protection schemes, it is difficult to select which key management or trust management schemes in a specific WSN application suit best. We did a detailed survey in our paper on how the properties of various trust management, authentication, and key management schemes can be used for specific applications. Based on this review, we present the methodologies, advantages, and limitations of the previously proposed key management, authentication, and trust management scheme in WSN. The goal of this thorough analysis is to compare and find the correct security solution that successfully meets the requirements of the application. Moreover, the strength, weaknesses, and open problems are added that can extend more frontiers to get the best security solutions in the future.s